Association of genetic variant and platelet function in patients undergoing neuroendovascular stenting. Issue 1103 (9th March 2017) - Li, Xin-Gang; Ma, Ning; Sun, Shu-Sen; Xu, Zhe; Li, Wei; Wang, Yong-Jun; Yang, Xin; Miao, Zhong-Rong; Zhao, Zhi-Gang
ABSTRACT: Introduction: The risk of recurrent ischaemic events is related to platelet function, which is often assessed by thromboelastography (TEG). TEG has high interindividual variability. Objective: To identify causal variants associated with TEG parameters in patients who receive aspirin and clopidogrel after intra- or extracranial stenting. Methods: Patients who underwent stenting for extracranial or intracranial stenosis (70–99%) were recruited into the study. Blood samples were obtained for TEG to assess the platelet function before stenting. Aspirin- and clopidogrel-related genetic polymorphisms were determined by the MassARRAY method. Minor allele frequency and Hardy–Weinberg equilibrium (HWE) tests and linkage disequilibrium (LD) analysis were carried out. The influences of genetic polymorphism on TEG parameters were analysed by linear regression. Results: A total of 249 patients were included in this study. Twenty-two selected single nucleotide polymorphisms (SNPs) were genotyped, and no significant deviation from HWE was found for any SNP in the study patients. Four SNPs—rs2104543, rs12772169, rs1998591 and rs1042194—within CYP2C18 were in high LD, and the genetic polymorphisms had a significant impact on the TEG parameters maximal clot strength (MAThrombin ) and ADP-induced platelet–fibrin clot strength (MAADP ). Patients who carried the loss-of-function CYP2C19*2 (rs4244285) allele were also at risk of increased MAThrombin and MAADP . Conclusions: Testing for these polymorphisms may be valuable in the identification of patients at high risk of recurrent ischaemic events. Alternative treatments may be considered for these high-risk patients. Trial registration number: NCT01925872